The Use of Online Social Media In Conducting Relationship Marketing On Tourist Decision to Visit (Case Study Tourism in the West Coast Regency of Lampung) - Khoiriyah, Siti; Munandar, Adis Imam (UI Scholars Hub, 2020)
To improve people welfare and national development, people can rely on the tourism sector. One of the areas that have a lot of tourism potential is the West Coast Regency of Lampung Province. Geographically, the location is stretching along the coast. The popularity of this tourist attraction can invite local and foreign tourists. This research will look at how the right marketing communication strategy to continue attracting the tourist's interest. One of them is by maintaining Relationship Marketing, especially in social media. This research aims at determining the form of Relationship Marketing, trust, and commitment to tourists, particularly in the use of social media in influencing tourist's decision to visit. The author uses a qualitative method with a case study approach, as well as digging information from the key informants on the West Coast Regency Tourism Office and the West Coast Regency Communication and Information Office. The author collects the data by conducting interviews, library research and documentation. As the analysis result and an in-depth study show that the right Relationship Marketing in developing tourism spot in the West Coast Regency is by developing trust and commitment to tourists. Social media is also needed to use actively to attract Millenials target.